ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF IMPLEMENTING THE MALUKU PROVINCE GOVERNMENT EXPENDITURE BUDGET FOR 2017-2021 - Frika Jessica Hitipeuw; Jozef R. Pattiruhu; Steven Siaila (SEAN Institute, 2023)
The research aims to assess the effectiveness of the implementation of the Maluku Province Regional Government expenditure budget for 2017-2021 and to assess the efficiency of implementing the Maluku Provincial Government expenditure budget for 2017-2021, with the type of research used in this research is descriptive which is studied quantitatively. The data analysis technique used in this study is effectiveness analysis, which describes the government's ability to realize the planned spending budget when compared to targets set based on the real potential of the region, and to analyze the level of efficiency of regional financial management in terms of expenditure, the ratio calculation formula between realization indirect expenditure budget to the total indirect expenditure budget. The results found that the level of effectiveness of the budget and spending each year varies with a tendency to increase in recent years. This is an indication of improved management seen in the increase in budget management in 2021. The ratio of budget and expenditure efficiency in 2017 was 85.79%, in 2018 the efficiency ratio was 87.46%, in 2019 the efficiency ratio was 91.09% , in 2020 the efficiency ratio is 69.04%, and in 2021 the efficiency ratio is 79.41%.